NEW ADSORBENTS DEVELOPED FROM NATURAL CLAYS TO REMOVE NI (II) FROM WASTEWATER - M. S. Kalmakhanova; Amantayevna A; Diaz Tuesta J.L; Seitbekova G.A; Darmenbaeva A.S; Reimbaeva S (Academic Scientific Journal of Chemistry, 2021)
Treatment of wastewater by adsorption is one of the most environmentally friendly methods, along with high efficiency. The main criteria when choosing materials for wastewater treatment by adsorption are its adsorption properties, porous structure and cost-effectiveness. Heavy metal ions are the main pollutants present in wastewater from machine-building, non-ferrous metallurgy and instrument-making enterprises, its removal being mandatory employing processes such as adsorption. This work deals with the development of materials based on natural clays and on pillared clays and further application in the the adsorption of Ni (II), used as model pollutant, from aqueous solution. The starting natural clay (montmorillonite) was obtained in a deposit of Kazakhstan (Asa), and two additional samples were prepared by treatment of the natural clay with acid and by pillarization with Fe2+ and Zn2+. Batch adsorption experiments were carried out to explore the effect of pH, adsorbent load, contact time and the initial ion concentrations of Ni (II) in the adsorption of the heavy metal from aqueous solution with the three adsorbent samples. A maximum removal of Ni (II) of 98.9% was achieved at pH 10 with a dose of adsorbent of 2 g/L, a contact time of 120 min and an initial concentration of metal ions of 50 mg/L, when considering the Asa natural clay